The Influence of Corporate Governance, Sharia Supervisory Board on Disclosure of Islamic Social Reporting (ISR) in Sharia Commercial Banks for the 2015-2018 Period - Jubaedah, Siti; Prianti, Umay (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
The purpose of this study is to obtain empirical evidence about the influence of institutional ownership, audit committees, and sharia supervisory boards on Islamic social reporting disclosure. The population in this study is Islamic commercial banks in Indonesia for the 2015-2018 period. The research method used is basic research with sample selection using purposive sampling method. The data used is the annual report of Islamic banks registered with the Financial Services Authority, published on www.ojk.co.id. The sample used in this study were 12 Islamic commercial banks so that 48 research data were obtained for the 2015-2018 period. Data were analyzed using multiple linear regression and the classical assumption test supported by SPSS version 23 for windows to test the direct effect of the independent variable on the dependent variable. Before conducting multiple linear regression analysis, the classical assumption test is performed. The classic assumption test is done with a normality test, a multicollinearity test, an autocorrelation test and a heteroscedasticity test. The results showed that Institutional Ownership, Audit Committee, Sharia Supervisory Board had no effect on Islamic Social Reporting Disclosure (ISR).